A novel and practical synthesis of Iclaprim. Issue 3 (1st February 2021) - Liu, Weiyuan; Chen, Liang; Pan, Jing; Zhou, Ting; Lin, Kuaile; Zhou, Weicheng
Abstract: A novel and facile synthesis of Iclaprim was reported. Started from trimethoprim (TMP), the amino-protection and Friedel–Crafts acetylation with acetic anhydride were simultaneously completed in CH2 Cl2 with SnCl4 as catalyst. The Knoevenagel condensation of 2, 4-diamino-5-(2-acetyl-3-hydroxy-4, 5-dimethoxybenzyl)pyrimidine with cyclopropyl carboxaldehyde followed by the intramolecular Michael addition in the buffer system (pyrrolidine and acetic acid) installed the key framework (chromanone 13). The dehydration was catalyzed by H2 SO4 so that the formation of 5-cyclopropyl-2, 3-dimethoxy-4, 5, 6, 6a, 7, 12-hexahydronaphtho[1, 8-bc]pyrimido[5, 4-f]azepin-9-amine, an impurity of Iclaprim reported at the first time, could be minimized. In the end, Iclaprim was obtained in a total yield of 21%. Graphical Abstract: